Detection of neuromechanical acute fatigue-related responses during a duathlon simulation: Is tensiomyography sensitive enough? - Rojas-Valverde, D; Sánchez-Ureña, B; Gómez-Carmona, C. D.; Ugalde-Ramírez, A.; Trejos-Montoya, A.; Pino-Ortega, J.; Gutiérrez-Vargas, R. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
New technological advances are constantly being developed to assess fatigue and muscle damage in sports. Tensiomyography (TMG) has been used as an alternative method to indirectly assess these physiological responses. The aim of this study was to explore the potential use of TMG parameters (muscle radial deformation [Dm], time of contraction [Tc], delay time [Td], deformation rate until 10% [V10] and 90% [V90]) to detect neuromuscular acute fatigue-related responses during a duathlon compared to well-known biochemical (blood lactate [BLa]), perceptual (rate of perceived exertion [RPE]), and functional (jump performance [CMJ]) variables. Twenty-three well-trained athletes (age 33.6 ± 7.2 years, weight 64.4± 9.2 kg, height 1.7 ± 0.2 m, VO2max 56.7± 6.9 mL/kg/min, body fat 16.6 ± 8.4%, lean mass 53.2 ± 11.6 kg) performed a 5k-25k-5k duathlon under controlled indoor conditions at 23°C. TMG muscle properties (left and right gastrocnemius lateralis), BLa, RPE, and CMJ were measured pre-duathlon, during transition 1 (T1), during transition 2 (T2), and post-duathlon. After one-way analyses of variance, there were large differences in BLa (p< 0.01), RPE (p< 0.01) and CMJ (p< 0.01). Large differences (p< 0.01) were also found in Tc, Dm, Td, V10, and V90 as TMG muscle mechanical markers. Compared to well-known fatigue variables (CMJ, RPE, and BLa), Tc and Dm as TMG parameters measured in gastrocnemius lateralis seem to be sensitive enough to detect acute fatigue-related changes during duathlon. Differences reported in Td, V10, and V90 could be the result of muscle post-activation potentiation (PAP) after T1, and more evidence is needed for understanding this PAP phenomenon using TMG.